Primary anastomosis for complete bulbar urethral rupture with rectal laceration caused by straddle injury: A case report. (May 2021) - Syarif,; Palinrungi, Muhammad Asykar; Kholis, Khoirul; Syahrir, Syakri; Pakan, Adriani Purnasakti; Faruk, Muhammad
Highlights: About 10% of traumatic injury patients have genitourinary involvement. Immediate exploration and urethral reconstruction is indicated in urethral trauma. Urethra rupture with anorectal laceration can be treated with primary anastomosis. Abstract: Introduction: The initial management of urethral trauma remains disputed, and there are several suitable techniques, including delayed repair and suprapubic urinary diversion as well as primary endoscopic or open alignments. The treatment choice used depends on the rupture's location and length as well as the accompanying trauma. Case presentation: A 33-year-old male patient was referred to the department of emergency, with the chief complaint of inability to void experienced 1 day before being admitted, after falling from a height of approximately three meters. There was a laceration to the perineum 3 cm long to the rectum, with no active bleeding. After the incident, the patient could not void, but the lower abdomen was not painful. Upon retrograde urethrography examination, contrast extravasation of the bulbous urethra was seen through the anorectal laceration. Immediate debridement and repair for the anorectal wound, then primary anastomosis for the bulbous urethra, was performed. Discussion: The likelihood of an injury to the anterior urethra increases with certain clinical features, including blood in the urethral meatus, palpable bladder distention, and a butterfly appearance on the perineum. Immediate exploration and reconstruction of the urethra is recommended in urethral traumas associated with penile fractures and non-life-threatening penetrating injuries. Furthermore, small lacerations are repaired primarily, while total ruptures are treated with anastomosis. Conclusion: Proper identification and management of urethral rupture determines the outcome. Initial urethral trauma management is disputed; however, a bulbous urethra rupture with anorectal lacerations can be treated safely and effectively with primary anastomosis.